Literature Study: The Influence of the Sorogan Method in Reading Classical Islamic Texts at the Al-Mizan Panongan Islamic Boarding School - shoimin, Royan Babush; Jamaludin, Gilang Maulana (Departement of PAI, Universitas Majalengka, 2025)
Considering that many students have difficulty understanding and reading the yellow book correctly, this article discusses how the Sorogan approach can be applied in reading the book. Among them are the lack of efficient teaching methods and the inability to read Arabic correctly. The main competency required by students in modern and traditional Islamic boarding schools is the ability to read the Yellow Book. Apart from that, it will be easier for children to read the yellow book using the Sorogan method. A literature review or library research method was used in this investigation. Content analysis is the data analysis method used. Reading the literature several times and comparing it to other works can maintain validity and reduce inaccurate information when assessing data.